Structural definition of babesial RAP-1 proteins identifies a novel protein superfamily across Apicomplexa - Isidro Hötzel; Carlos E. Suarez (Scientific Reports, 2023)
Abstract Apicomplexan protozoa are intracellular parasites of medical and economic importance. These parasites contain specialized apical complex organelles, including rhoptries, that participate in the process of host cell invasion. Conserved antigens expressed in the rhoptries are rational vaccine targets, but whether conservation of protein structure is a functional requirement for invasion remains unknown. Novel protein structural modeling enables identification of structurally conserved protein families that are not evident by sequence analysis alone. Here we show by AlphaFold2 structural modeling that the rhoptry-associated protein 1 superfamily of the Piroplasmida hemoparasites Babesia and Theileria (pRAP-1) is structurally conserved, with the core conserved region being composed of a globin-like and a 4-helix bundle subdomain. Search for structurally related members of this protein family in other apicomplexan parasites revealed structural homologues of pRAP-1 in several species of Plasmodium, Toxoplasma gondii and other members of the Sarcocystidae family. Based on these structural findings, pRAP-1 is a conserved apical complex protein, but whether these proteins share functional features in different species remains unknown. Identification of widely conserved elements involved in infection in these parasites will enhance our knowledge of invasion mechanisms, and facilitate the design of methods for controlling diseases that affect humans and animals globally.